1998
DOI: 10.1002/(sici)1097-4644(19980501)69:2<95::aid-jcb1>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Induction of interleukin (IL)-1α and β gene expression in human keratinocytes exposed to repetitive strain: Their role in strain-induced keratinocyte proliferation and morphological change

Abstract: Recent studies in our laboratory have demonstrated that mechanical strain alters many facets of keratinocyte biology including proliferation, protein synthesis, and morphology. IL-1 is known to play an important role in the autocrine regulation of these basic cellular properties under basal and stimulated conditions. However, it is not known whether IL-1 plays a role in strain-induced alteration of keratinocyte biology. Thus, the objective of this study was to test the hypothesis that cyclic strain stimulates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 32 publications
2
9
0
Order By: Relevance
“…These results correspond well to studies performed by Lee et al. and Takei et al., which showed that the mechanical straining of keratinocyte monolayers promotes the expression and release of IL‐1 α and IL‐1RA (9,33). An increase in cytokines, such as IL‐1 α and TNF‐ α was also found in studies in which the epidermal tissue was irritated and/or injured by applying various chemicals, UV irradiation or by tape stripping (14,34–39).…”
Section: Discussionsupporting
confidence: 92%
“…These results correspond well to studies performed by Lee et al. and Takei et al., which showed that the mechanical straining of keratinocyte monolayers promotes the expression and release of IL‐1 α and IL‐1RA (9,33). An increase in cytokines, such as IL‐1 α and TNF‐ α was also found in studies in which the epidermal tissue was irritated and/or injured by applying various chemicals, UV irradiation or by tape stripping (14,34–39).…”
Section: Discussionsupporting
confidence: 92%
“…25,29 These mechanisms are partially controlled by quick cytokine release to the body fluid from residual cells. [30][31][32][33] Indeed, IL-1 release has already been reported in stretched keratinocytes, 34 supporting our results and validating the keratinocyte mechanosensation in the presented system. Moreover, some cytokines such as IL-1b, IL-6 or TNF-a have already been reported to contribute to the pathogenesis of skin disorders related to mutations in keratin genes, such as epidermolysis bullosa simplex (EBS).…”
Section: Discussionsupporting
confidence: 89%
“…In addition to growth factors, which are known to mediate the proliferation and differentiation of keratinocytes (35), mechanical stress has also been assumed to cause alterations in their proliferation and was shown to affect cell growth in vitro (5,36). Several signalling pathways were found to be altered by mechanical stimulation including isoform‐specific PKC activation (37) and induction of interleukin‐1 α and β gene expression (38). Recent experiments established a link between hyperosmotic stress and reduced proliferation rate in HaCaT (39) as well as by resveratrol‐induced cell cycle arrest in p53 mutant keratinocytes (40).…”
Section: Discussionmentioning
confidence: 99%